A Building-Material Supply Chain Sustainable Operations under Fairness Concerns and Reference Price Benefits. (19th April 2021) - Xiao, Huimin; Xu, Youlei; Li, Shiwei
Abstract : This paper incorporates fairness concerns and consumer reference price effects into a two-echelon building-material closed-loop supply chain consisting of a manufacturer and a retailer. By establishing four differential game models, we investigate the sustainable operations and cooperation of this supply chain. The four game models are a Nash noncooperative game, Stackelberg game with cost sharing, Stackelberg game with fairness concerns and cost sharing, and centralized decision model. By using dynamic models and optimal control theory, we obtain the two members' optimal equilibrium strategies in the supply chain. Analytical results show that the consumer reference price effect has a positive impact on the manufacturer's effort level, retailer's publicity level, and product brand goodwill, which can improve the supply chain performance. The retailer's partial commitment to cost sharing can enhance the production enthusiasm of the manufacturer, improve the brand reputation of the product, and enhance the two members' individual profitability. The distributional fairness concerns of the manufacturer not only prevent the manufacturer and retailer from achieving Pareto improvement but also lead to the decline of the manufacturer's effort level and profitability. The research conclusions of this paper can provide some insights into the cooperation and sustainable development of the supply chain.